A change management toolkit originated from China. (1st January 2013) - Lan, Ping
Among all management toolkits originated from China, I Ching may be the least known one to the Western world, due to its polar opposite to conventional Western management philosophy and methodology. Based on analysing the working mechanism and its functionality in providing an unbounded 'result-process-advice' set for dealing with uncertainty, this paper focuses on the linkage of the I Ching idea and modern management philosophy and tactics. It examines the differences and similarities of the two ways in areas such as theory, method, perspective on change, solution formulation and tactics deployment. It argues that the both toolkits are useful in dealing with changes. While going with the Western routine, having some ideas outside the causal link enables managers to better prepare for uncertainty. While going with the I Ching routine, having a causal link to fill the vagueness of different unrelated situations will make more sense.